Table Tennis - Kuman, ashok (New Delhi, 1999)
This book seeks to get positive response as means by which sports can promote and propagate peace and international cooperation. Sportsmen form a large identifiable cadre. We visualises a situation where a conscious efforts is made all over the world to train the sportsperson to spread the message of peace and international cooperation. Instead of peace keeping efforts through arms and army, the sportsperson may be used as solders of peace in a subtle manner. The effort is to make the realize the contribution of sports as a factor for sustainable development, peace keeping and international cooperation. This book will be useful to the sports promoters, organisers, coaches and other persons related or interested in sports.
Keywords: Table Tennis